Market Entry Opportunities for a Music Artist - Kepalienė, Inga; Birutė Žygaitienė; Gaudrė Semėnaitė (Technium Social Sciences Journal, 2024)
A music artist whose goal is to succeed in the music market needs to understand what the opportunities are. The music market is developed and full of a wide range of music artists that meet the expectations of different consumers. Every year, new music artists enter the music market, looking for opportunities to expand the recognition of their name as a brand and of their work. The aim of this paper is to find out what are the market entry opportunities for a music artist by analysing information and scientific sources and interviewing experienced music managers.